Grid Voltage Dip Impacts on the DFIG Wind Turbine and Its Main AC Contactor Performances - Ahsein Jomaa Alshibani; Rini Nur Hasanah; Hadi Suyono (Fakultas Teknik, Universitas Brawijaya, 2018)
Doubly-fed induction generators connected to the power grid are widely used in wind farms as a part of the power system. The wind turbines are in general susceptible to grid disturbance in a form of transient faults which often result in voltage dips. The DFIGs are connected to the grid via conductors whose operating mechanism depends on the grid voltage through an auxiliary transformer. This paper discusses the effects of grid voltage dips on the doubly-fed induction generator and its main contactor. The study focuses on the modeling and simulation of a doubly-fed induction generator and a wind turbine connected to the grid through ac contactors. The model is subjected to various symmetrical voltage dips and their effects on the grid contact mechanism of the DFIG generator during these transient faults are explored to find out the minimum voltage dip which still keeps the contactor engaged. The impacts of the grid transients on the performance behaviour of the doubly-fed induction generator are also observed.